2020
DOI: 10.1021/acsami.0c15734
|View full text |Cite
|
Sign up to set email alerts
|

Wetting-Induced Fabrication of Graphene Hybrid with Conducting Polymers for High-Performance Flexible Transparent Electrodes

Abstract: Graphene has attracted extensive attention for the supply of electrically conductive, optically transparent, and mechanical robust electrodes for flexible optoelectrical devices, as an alternative to commercial indium tin oxide, due to its superior mechanical, electrical, and optical properties. However, conventional chemical vapor deposition is impeded by harsh conditions and complicated processes, and it is still a challenge to fabricate high-performance graphene transparent electrode in a facile and scalabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 69 publications
1
14
0
Order By: Relevance
“…Among them, the Δ T values of FECD-5Nets and FECD-4Nets retain high optical modulation of more than 60% and high Δ T retention of about 95% compared with the initial optical modulations. Although there is still a small gap with few reported ECDs, the FECD-5Nets show good comprehensive performance compared with most of the reported organic-based wearable ECDs in the last 4 years (Figure e). …”
Section: Resultsmentioning
confidence: 89%
“…Among them, the Δ T values of FECD-5Nets and FECD-4Nets retain high optical modulation of more than 60% and high Δ T retention of about 95% compared with the initial optical modulations. Although there is still a small gap with few reported ECDs, the FECD-5Nets show good comprehensive performance compared with most of the reported organic-based wearable ECDs in the last 4 years (Figure e). …”
Section: Resultsmentioning
confidence: 89%
“…proposed a wetting‐induced scalable solution‐processable approach to fabricate a hybrid film of graphene with conductive ionogel and PEDOT:PSS. [ 80 ] The graphene/ionogel@PEDOT:PSS hybrid film achieved a low R sh of 30 Ω sq −1 and a high Tr of 88%@550 nm wavelength (Figure 8e,f). At the same time, it showed the low surface roughness as well as good flexibility that nearly no change after bending 1500 times.…”
Section: Fabrication Properties and Modification Of Cvd‐grown Graphenementioning
confidence: 99%
“…The red star in (f) means the performance of G/ionogel@PEDOT:PSS trinary hybrid film, which was superior to pristine graphene and ITO films on PET substrate. e,f) Reproduced with permission [80]. Copyright 2020, American Chemical Society.…”
mentioning
confidence: 99%
“…In order to further understand the interface behavior of composites, Cui et al simulated the contact behavior of CNTs and AgNWs at the atomic scale using molecular dynamics simulations, which showed that the CNTs and AgNWs move toward each other and then form a complete interfacial arrangement [121]. Ma et al prepared graphene/ionic gel @PEDOT:PSS using a solution treatment, which was applied as a transparent electrode to obtain a low thin layer resistance of 30 Ω•sq −1 and a high transmittance of 88% [122]. Kim et al reported a way to improve the electrical conductivity of graphene by doping it with metal selective atomic layer deposition (ALD) (Figure 10).…”
Section: Composite Materialsmentioning
confidence: 99%